Differences in the structure and functionalities of graphene oxide and reduced graphene oxide obtained from graphite with various degrees of graphitization. (May 2022) - Bychko, Igor; Abakumov, Alexander; Didenko, Olga; Chen, Mengyao; Tang, Jianguo; Strizhak, Peter
Abstract: Reduced graphene oxide (rGrO) is a promising graphene derivative that attracts attention due to its unique properties. The well-established route to obtain rGrO is a reduction of graphene oxide (GrO) produced by graphite oxidation. In this paper, we demonstrate the correlation between the structure of pristine graphite and the structural and catalytic properties of synthesized GrO and rGrO. We use TEM, SEM, DLS, XRD, FTIR, Raman, XPS, and nitrogen adsorption-desorption to characterize various pristine graphites and synthesized GrOs and rGrOs. These studies show that the formation of different nitrogen-containing groups in rGrO is associated with the treatment of GrO with hydrazine. Catalytic properties of pristine graphites and rGrOs were determined in the hydrogenation of the p-nitrotoluene by molecular hydrogen. Results of this work can provide a new idea that the crystallinity of graphite, quantified by a degree of graphitization, serves as the clue parameter influencing the structure, surface functionality, and catalytic properties of rGrO. We hope that this article will contribute a new insight for the synthesis of rGrO with pronounced properties not only for catalytic applications but also for energy storage due to the possibility of governing rGrO properties by a selection of more suitable pristine graphite. Graphical abstract: Image 1 Highlights: The structure of graphite correlates with the structure of synthesized graphene oxide and reduced graphene oxide. Catalytic activity in the hydrogenation of the p-nitrotoluene demonstrated. Degree of graphitization influences the structure, surface functionality, and catalytic properties.